Rare solid tumors in a patient with Wiskott–Aldrich syndrome after hematopoietic stem cell transplantation: case report and review of literature - Coppola, Emma; Giardino, Giuliana; Abate, Massimo; Tambaro, Francesco Paolo; Bifano, Delfina; Toriello, Elisabetta; De Rosa, Antonio; Cillo, Francesca; Pignata, Claudio; Cirillo, Emilia (Frontiers in Immunology, 2023)
Wiskott Aldrich syndrome (WAS) is an X-linked recessive primary immunodeficiency disorder characterized by severe eczema, recurrent infections and micro-thrombocytopenia. Allogeneic hematopoietic stem cell transplantation (HSCT) is a potentially curative therapeutic option for patients with classic form. The risk of developing post-transplant tumors appears to be higher in patients with WAS than in other Inborn errors of immunity (IEIs), but the actual incidence is not well defined, due to the scarcity of published data. Herein, we describe a 10-years-old patient diagnosed with WAS, treated with HSCT in the first year of life, who subsequently developed two rare solid tumors, kaposiform hemangioendothelioma and desmoid tumor. A review of the literature on post HSCT tumors in WAS patients has been performed. Patient received diagnosis of classic WAS at the age of 2 months (Zhu score = 3), confirmed by WAS gene sequencing, which detected the nonsense hemizygous c.37C>T (Arg13X) mutation. At 9 months, patient underwent HSCT from a matched unrelated donor with an adequate immune reconstitution, characterized by normal lymphocyte subpopulations and mitogen proliferation tests. Platelet count significantly increased, even though platelets count never reached reference values. A mixed chimerism was also detected, with a residual WASP- population on monocytes (27.3%). Patient developed a kaposiform hemangioendothelioma at the age of 5. A second abdominal tumor was identified, histologically classified as a desmoid tumor when he reached the age of 10 years. Both hematopoietic and solid tumors were identified in long term WAS survivors after HSCT. Here we describe the case of a patient with WAS who developed two rare solid tumors after HSCT. An active surveillance program for the risk of tumors is necessary in the long-term follow-up of post-HSCT WAS patients.